Intergenerational Persistence in the Effects of Compulsory Schooling in the US - Titus Galama; Andrei Munteanu; Kevin Thom (Tinbergen Institute, 2024)
Using linked records from the 1880 to 1940 full-count United States decennial censuses, we estimate the effects of parental exposure to compulsory schooling (CS) laws on the human capital outcomes of children, exploiting the staggered roll-out of state CS laws in the late nineteenth and early twentieth centuries. CS reforms not only increased the educational attainment of exposed individuals, but also that of their children. We find that one extra year of maternal (paternal) exposure to CS increased children's educational attainment by 0.015 (0.016) years - larger than the average effects on the parents themselves, and larger than the few existing intergenerational estimates from studies of more recent reforms. We find particularly large effects on black families and first-born sons. Exploring mechanisms, we find suggestive evidence that higher parental exposure to CS affected children's outcomes through higher own human capital, marriage to more educated spouses, and a higher propensity to reside in neighborhoods with greater school resources (teacher-to-student ratios) and with higher average educational attainment.
Keywords: I1; I2; I24; I25; I26; 330; Education; Economic Development; Returns to Education